Theoretical Study of Stereodynamics for the $S+H_2 \ (υ=0$-$2, j=0)→ SH+H$ Reaction (Journal of Atomic and Molecular Sciences, 2022)
Quasi-classical trajectory (QCT) calculations for the reaction $S+H_2(v=0$-$2,j=0) → SH+H$ have been performed in order to investigate the effect of initial vibrationalstates on both the scalar and vector properties. The integral cross sections, opacityfunction have been calculated. The results indicate that the reaction probability andthe cross section increase as the initial vibrational quantum number increases. Thevibrational distributions and rotational distributions at different vibrational excitedstates are presented, and the results are discussed in detail. In addition, the vectorproperties, involving scattering directions of reaction product and the alignment andorientation of rotational angular momentum, are calculated and discussed. The resultsindicate that the vibrational excited states have a positive effect on the forward scatteringdirection of the product, and the vibrational excited states have slight effect on thealignment and orientation of the rotational angular momentum.